Carbon-based thin film dual-mode water-vibration power generation system and method based on work function difference regulation
Patent Information
- Application Number
- CN202610882622.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-18
- Publication Date
- 2026-10-09
AI Technical Summary
[0006]鉴于现有技术中存在单个器件输出能力有限、难以兼顾液态水环境与空气湿气环境以及模块化集成适用性不足等问题,本发明的目的在于提供一种基于功函数差调控的碳基薄膜双模式水伏发电系统与方法,以提高器件在不同含水环境下的适用性及模块化集成能力
(1)本发明通过对两个相邻的碳基薄膜实施差异化表面调控处理,在两者之间构建功函数差,有利于形成不对称界面,从而实现对器件输出行为的调控。
Smart Images

Figure CN122890919A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of environmental energy harvesting and hydroelectric power generation technology, specifically to a carbon-based thin-film dual-mode hydroelectric power generation system and method based on work function difference regulation. Background Technology
[0002] Hydrovoltaic power generation technology is an energy harvesting technology that utilizes the interaction between water and functional materials to generate electricity. It can be applied to fields such as environmental energy harvesting, self-powered sensor devices, and powering flexible electronic devices. Compared with traditional hydropower utilization methods that rely on large mechanical devices, hydrovoltaic power generation devices typically have the advantages of lightweight structure, ease of miniaturization, and suitability for flexible applications, thus attracting widespread attention.
[0003] Existing hydroelectric power generation systems have been studied in systems using porous carbon materials, metal oxides, polymer materials, and their composites, and can achieve certain electrical outputs under conditions such as liquid water, humidity, water droplets, evaporation, and waves. However, existing technologies still have the following problems: First, the output voltage and current of individual devices are generally low, making it difficult to directly meet the needs of practical applications; second, existing devices are mostly designed for single water-containing environments, making it difficult to ensure stable output in both liquid water and humid air environments; third, during device integration, differences in unit structure, insufficient output consistency, and limited environmental adaptability often affect the overall output performance and modular application effectiveness.
[0004] Furthermore, current research on factors influencing the output of water-based photovoltaic (PV) devices largely focuses on wettability, pore structure, surface functional groups, and ion transport conditions. However, the differences in electronic structure between different functional thin films, especially the work function difference, have not been fully utilized in regulating device output behavior. The lack of a unified design approach applicable to both liquid water and humid air environments hinders clear guidance for device structure optimization and performance control, thus limiting the expanded application of PV devices under varying water content conditions.
[0005] Therefore, it is necessary to provide a dual-mode hydrovoltaic power generation system and method, which can achieve effective output in both liquid water driven mode and air-humidity driven mode by constructing an asymmetric carbon-based thin film interface with a work function difference, thereby improving the applicability and modular integration capability of the device in different water-containing environments. Summary of the Invention
[0006] In view of the problems in the existing technology, such as the limited output capability of a single device, the difficulty in taking into account both liquid water environment and air humidity environment, and the insufficient applicability of modular integration, the purpose of this invention is to provide a carbon-based thin film dual-mode hydrovoltaic power generation system and method based on work function difference regulation, so as to improve the applicability of the device in different water-containing environments and the modular integration capability.
[0007] To achieve the above objectives, the present invention provides a carbon-based thin-film dual-mode hydrovoltaic power generation system based on work function difference regulation, comprising several carbon-based thin films, wherein an aqueous medium is disposed between two adjacent carbon-based thin films. Two adjacent carbon-based thin films undergo different surface conditioning treatments to create a power function difference between them. Several carbon-based thin films are respectively brought into contact with an aqueous medium to form an interface, and then connected to an external circuit to form a hydroelectric power generation system; The hydroelectric power generation system has a liquid water driven power generation mode and an air moisture driven power generation mode; when it is a liquid water driven power generation mode, the water-containing medium is liquid water, and when it is an air moisture driven power generation mode, the water-containing medium is a non-ionic hygroscopic hydrogel.
[0008] This invention also provides a method for preparing the above-mentioned carbon-based thin-film dual-mode hydrovoltaic power generation system based on work function difference regulation, comprising the following steps: A methanol solution containing polyethyleneimine was applied to the surface of a conductive carbon-based material sheet and dried to obtain a first carbon-based thin film. A conductive carbon-based material sheet is immersed in an acid solution at room temperature; after immersion, the conductive carbon-based material sheet is washed until neutral and then dried to obtain a second carbon-based film. Polyvinyl alcohol, glycerin and deionized water are mixed and heated to dissolve, then poured into a mold to cool and solidify into a gel, resulting in a nonionic hygroscopic hydrogel. A dual-mode hydrovoltaic power generation system is obtained by alternately setting up several first carbon-based thin films and several second carbon-based thin films, and placing a non-ionic hygroscopic hydrogel between the first carbon-based thin films and the second carbon-based thin films.
[0009] Compared with the prior art, the present invention has at least the following beneficial effects: (1) The present invention implements differential surface conditioning treatment on two adjacent carbon-based thin films to construct a work function difference between them, which is conducive to forming an asymmetric interface, thereby realizing the control of the device output behavior.
[0010] (2) The present invention uses the power function difference as the design basis of the dual-mode hydrovolt power generation system, so that the same inventive concept can be applied to both liquid water drive mode and air moisture drive mode, which helps to broaden the application scenarios of the device.
[0011] (3) The present invention uses conductive carbon-based thin film and water-containing medium to construct a hydrovoltaic power generation system. The device structure is relatively simple and it is easy to achieve modular integration through series and / or parallel connection to meet different output voltage and output current requirements.
[0012] (4) The materials used in this invention are widely available and the preparation process is relatively simple, which has certain potential for flexible application and practical application value. Attached Figure Description
[0013] Figure 1 This is a schematic diagram of the structure of the carbon-based thin-film dual-mode hydrovoltaic power generation system based on work function difference control according to the present invention.
[0014] Figure 2 This is a comparison chart of the output voltage of the liquid water-driven hydrovoltaic power generation system (C-HEG) before and after surface conditioning treatment.
[0015] Figure 3 The figure shows the test results of the influence of the composition and surface modification conditions of the first carbon-based thin film material on the output performance of the liquid water driven hydroelectric power generation system (C-HEG); among them, Figure 3 In the figure, 'a' represents a comparison of the output performance of the first carbon-based thin film prepared using different conductive carbon-based materials. Figure 3 In the figure, b represents a comparison of output performance using different concentrations of polyethyleneimine modification. Figure 3 In the figure, c represents a comparison of the output performance of the first carbon-based thin film prepared using different carbon black materials.
[0016] Figure 4 The figure shows the test results of the effect of the second carbon-based thin film surface conditioning conditions on the output performance of the liquid water driven hydroelectric power generation system (C-HEG); among them, Figure 4 In the figure, 'a' represents a comparison of the output performance of the second carbon-based thin film treated with different concentrations of nitric acid. Figure 4 Figure b in the figure shows a comparison of the output performance of the second carbon-based thin film treated with different oxidation modifications. Figure 4 In the figure, c represents a comparison of the output performance of the second carbon-based thin film treated with different acid solutions.
[0017] Figure 5 The figure shows the test results of the output performance and structural parameters of the optimized liquid water-driven hydroelectric power generation system (C-HEG); among them, Figure 5 In the figure, 'a' represents the test results of open-circuit voltage and short-circuit current density. Figure 5 In the figure, b is a comparison chart of output performance under different water source conditions. Figure 5 In the figure, 'c' represents the test results of the effect of the distance between the first and second carbon-based films on the output performance.
[0018] Figure 6 The figure shows the output performance, structural parameters, and environmental adaptability test results of the air-humidity driven hydroelectric power generation system (C-MEG); among them, Figure 6 Figure 'a' in the graph represents the output performance test results under conditions of 25 ℃ and 60% relative humidity. Figure 6 In the figure, b represents the test results of the effect of polyvinyl alcohol / glycerol hydrogel thickness on output performance. Figure 6 In the figure, 'c' represents the test results of the effect of active area on output performance. Figure 6 In the figure, d represents the variation of output current density under different environmental humidity conditions.
[0019] Figure 7 The figure shows the output performance test results of multiple air-moisture driven hydroelectric power generation systems (C-MEG) after modular integration; among them, Figure 7 In the figure, 'a' represents the output voltage test result after series connection. Figure 7 In the figure, b represents the output current test results after parallel connection. Figure 7 The figure shows the output voltage test results of the stacked array.
[0020] Figure 8 This is a schematic diagram illustrating the flexibility, storage stability, and configuration of a moisture-driven hydroelectric power generation system (C-MEG); among which, Figure 8 In the figure, 'a' represents the output stability test graph under straight, bent, and torsional conditions. Figure 8 In the graph, b represents the output retention rate test results after the power generation membrane has been stored for a certain period of time. Figure 8 In the diagram, 'c' represents a schematic diagram of different geometric shapes or configurations of the dual-mode hydro-voltaic power generation module.
[0021] Figure 9 A schematic diagram illustrating the application of multiple liquid water-driven hydroelectric power generation systems (C-HEG) connected in series to charge a capacitor and drive a small fan.
[0022] Figure 10 A schematic diagram illustrating the application of multiple air-moisture-driven hydroelectric power generation modules (C-MEG) connected in series to power an electronic watch.
[0023] Reference numerals: 1. First carbon-based thin film; 2. Second carbon-based thin film; 3. Aqueous medium; 4. External circuit. Detailed Implementation
[0024] The present invention will be further described below with reference to the accompanying drawings and specific embodiments. It should be understood that the following embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the scope of protection of the present invention. Equivalent substitutions, modifications, or improvements made by those skilled in the art based on the content of the present invention without departing from the concept of the present invention should all fall within the scope of protection of the present invention.
[0025] Since the key to this invention lies in utilizing the difference in work function between different carbon-based materials, regardless of whether the number of thin films is two, three, or more, as long as the core condition of a work function difference exists at the interface of any two adjacent carbon-based thin films is met, the power generation objective of this invention can be achieved. Therefore, the following embodiments use two carbon-based thin films as an example.
[0026] Example 1 This embodiment provides a carbon-based thin-film dual-mode hydrovoltaic power generation system based on work function difference regulation. Please refer to [link to documentation]. Figure 1 The system includes a first carbon-based thin film 1, a second carbon-based thin film 2, and an aqueous medium 3 disposed between the first carbon-based thin film 1 and the second carbon-based thin film 2; The surface conditioning treatment of the first carbon-based thin film 1 is amine polymer surface modification, and the surface conditioning treatment of the second carbon-based thin film 2 is oxidation modification treatment. By subjecting the first carbon-based thin film 1 and the second carbon-based thin film 2 to different surface conditioning treatments, a power function difference is formed between the two. The first carbon-based thin film 1 and the second carbon-based thin film 2 respectively contact the aqueous medium 3 to form a solid-liquid interface. The aqueous medium 3 forms an internal ion transport channel, and the external circuit 4 forms an external electron transport channel, thereby constituting a hydrovoltaic power generation system. In this embodiment, the difference in work function between the first carbon-based thin film 1 and the second carbon-based thin film 2 after differential surface treatment leads to an interfacial difference between the films, thereby forming a directional electrical output in the presence of an aqueous medium. When the aqueous medium is liquid water, the system operates in liquid water driven mode; when the aqueous medium is a hygroscopic material, the system operates in air moisture driven mode. The hygroscopic material is preferably a polyvinyl alcohol / glycerol nonionic hydrogel.
[0027] In the liquid water driven mode, the first carbon-based film and the second carbon-based film maintain a preset distance and come into contact with liquid water to form a liquid water driven photovoltaic power generation system; in the air moisture driven mode, the first carbon-based film, the moisture-absorbing material and the second carbon-based film are stacked in sequence to form an air moisture driven photovoltaic power generation system.
[0028] Preferably, in the liquid water driven mode, the spacing between the two carbon-based thin films is 5 mm, and the effective overlap area of the electrodes is 1 cm. 2 In the air-humidity driven mode, the thickness of the moisture-absorbing material sandwiched between the two films is 2 mm.
[0029] In the air-humidity driven mode, the nonionic hygroscopic hydrogel (such as polyvinyl alcohol / glycerol hydrogel) itself does not contain significant free ions. However, this hydrogel has strong hygroscopic properties and can continuously absorb water vapor from the ambient air. The absorbed water molecules naturally contain a very small amount of H+ generated by self-ionization. + and OH - (The ion product constant of water is 10) -14 Meanwhile, dissolved carbon dioxide in the air reacts with water to form carbonic acid, which in turn ionizes to release HCO3-. - and H +This further increases the ion concentration in the hydrogel. These trace ions have a certain migration ability in the aqueous network structure of the hydrogel.
[0030] When there is a work function difference between the first and second carbon-based thin films, their Fermi levels are different, resulting in an internal electric field when they are connected by a hydrogel (aqueous medium). Mobile ions in the hydrogel (mainly H+) + and OH - Driven by the built-in electric field, the hydrogel undergoes directional migration, thereby generating a current output in the external circuit. Experiments show that even hydrogels prepared with strictly deionized water can still produce significant output (e.g., Figure 6 As shown in the figure, this confirms the rationality of the above-mentioned "self-generated ion" mechanism.
[0031] Example 2 This embodiment provides a preferred method for preparing a first carbon-based film. The first carbon-based film is a polyethyleneimine-modified Ketjen black-loaded nonwoven film.
[0032] Non-woven fabric was selected as the flexible substrate and cut into 3×9 cm pieces. 2 The long strips are ultrasonically cleaned with ethanol and then rinsed with deionized water before being put into use. Weigh 0.95 g of Ketjen black and 1.07 g of sodium dodecylbenzenesulfonate and add them to 100 mL of deionized water. Use a probe-type ultrasonic treatment for 60 min to obtain a uniform and stable Ketjen black dispersion. The pretreated nonwoven fabric was immersed in the Ketjen black dispersion and fully impregnated under continuous stirring at 600 rpm, and then dried at 65 ℃ for 45 min. The impregnation-drying cycle was repeated 5 times to obtain a Ketjen Black loaded nonwoven film. Subsequently, a 5% (w / v) polyethyleneimine methanol solution was prepared and ultrasonicated for 1 h to ensure uniform dispersion. 900 μL of the polyethyleneimine methanol solution was then uniformly drop-coated onto a 3 × 9 cm plate. 2 The surface of the Kojtsen Black-loaded nonwoven film corresponds to a solution volume of approximately 0.33 L·m. -2 The film was dried under vacuum at 70 °C for 30 min to obtain a polyethyleneimine-modified Ketjen black loaded nonwoven film.
[0033] The film obtained in this embodiment is used as a preferred first carbon-based film.
[0034] Example 3 This embodiment provides a first carbon-based film comparison example without amine polymer modification, for comparison with the first carbon-based film modified with polyethyleneimine obtained in Example 2.
[0035] Non-woven fabric was selected as the flexible substrate and cut into 3×9 cm pieces. 2 The long strips are ultrasonically cleaned with ethanol and then rinsed with deionized water before being put into use. Weigh 0.96 g of Ketjen black and 0.92 g of sodium dodecylbenzenesulfonate and add them to 100 mL of deionized water. Use a probe-type ultrasonic treatment for 60 min to obtain a uniform and stable Ketjen black dispersion. The pretreated nonwoven fabric was immersed in the Ketjen black dispersion and thoroughly impregnated under continuous stirring at 500 rpm, and then dried at 60 ℃ for 60 min. The impregnation-drying cycle was repeated 6 times to obtain a Ketjen black loaded nonwoven film.
[0036] The thin film obtained in this embodiment was not modified with polyethyleneimine, and can be used to verify the effect of amine polymer surface modification on the work function of the first carbon-based thin film and the output performance of the device.
[0037] Example 4 This embodiment provides a method for preparing a first carbon-based thin film with different polyethyleneimine modification concentrations, to illustrate the effect of polyethyleneimine concentration on the output performance of the first carbon-based thin film and the corresponding hydroelectric power generation system.
[0038] Following the preparation method of Ketjen black-loaded nonwoven film in Example 2, Ketjen black-loaded nonwoven films were prepared. Subsequently, their surfaces were modified with 1% (w / v) and 12.5% (w / v) polyethyleneimine methanol solutions, respectively.
[0039] When using a 1% (w / v) polyethyleneimine methanol solution for modification, 900 μL of the polyethyleneimine solution is uniformly drop-coated onto a surface measuring 3 × 9 cm. 2 The surface of the nonwoven film loaded with Ketjon black was dried under vacuum at 70 °C for 20 min to obtain a 1% polyethyleneimine-modified Ketjon black-loaded nonwoven film.
[0040] When using a 12.5% (w / v) polyethyleneimine methanol solution for modification, 900 μL of the polyethyleneimine solution was uniformly drop-coated onto a surface measuring 3 × 9 cm. 2 The surface of the nonwoven film loaded with Ketjen black was dried under vacuum at 70 °C for 120 min to obtain a Ketjen black-loaded nonwoven film modified with 12.5% polyethyleneimine.
[0041] Comparing the film obtained in this embodiment with the 5% polyethyleneimine-modified film obtained in Example 2 can help determine the preferred range of polyethyleneimine modification concentration. Preferably, the polyethyleneimine mass-volume concentration is 5% (w / v).
[0042] Example 5 This embodiment provides two different conductive carbon-based materials as alternatives to the first carbon-based thin film.
[0043] In one approach, a first carbon-based thin film is prepared using carbon nanotubes as the conductive carbon-based material. The preparation process is as follows: Take 0.04g of carbon nanotube powder and 0.16g of polyvinylidene fluoride powder to form a mixed material, dissolve it in 16mL of N,N-dimethylformamide, heat and stir at 50℃ for 30min using a magnetic stirrer at 1000rpm to obtain a mixed solution; The mixed solution was placed in a 25% power ultrasonic cell disruptor for 60 min of ultrasonic treatment with an interval of 1.6 s to obtain the treated solution. The treatment solution was transferred onto a glass slide, and the glass slide was dried in an 80°C oven for 60 min to obtain a smooth, dark gray film that adhered tightly to the glass slide. After placing the film tightly attached to the glass slide into 500 mL of ethanol for 5 minutes, it was removed and peeled off from the edge using pointed tweezers to obtain a complete carbon nanotube composite film. Subsequently, a solution of polyethyleneimine and N,N-dimethylformamide with a mass-volume concentration of 2.5% (w / v) was prepared and ultrasonicated in a 25% power ultrasonic cell disruptor for 1 h to disperse them evenly. Take 900 μL of the polyethyleneimine solution and uniformly drop it onto a surface measuring 3 × 9 cm. 2 The surface of the carbon nanotube composite film corresponds to a solution volume of approximately 0.33 L / m. -2 The carbon nanotube composite film modified with polyethyleneimine was obtained by drying it under vacuum at 120℃ for 5 min.
[0044] In another approach, a first carbon-based thin film is prepared using commercially available graphite film as the conductive carbon-based material. The preparation process is as follows: Commercial graphite film was selected as the substrate and cut into 3×9 cm pieces. 2 The long strips are cleaned with ethanol and then dried to obtain the pretreated original graphite film. Subsequently, a solution of polyethyleneimine and N,N-dimethylformamide with a mass-volume concentration of 2.5% (w / v) was prepared and ultrasonicated in an ultrasonic cell disruptor at 25% power for 1 h to disperse them evenly. Take 900 μL of the polyethyleneimine solution and uniformly drop it onto a surface measuring 3 × 9 cm. 2 The original graphite film surface corresponds to a solution volume of approximately 0.33 L / m. -2 The graphite film modified with polyethyleneimine was dried under vacuum at 70°C for 20 min to obtain the graphite film.
[0045] This embodiment illustrates that, in addition to carbon black-loaded nonwoven films, carbon nanotube composite films and graphite films can also be used as first carbon-based films modified with amine polymers.
[0046] Example 6 This embodiment provides a scheme for preparing a first carbon-based thin film using different carbon black materials. In addition to the scheme in Example 2, there are five other schemes, including those using independent carbon black materials and mixed carbon black materials.
[0047] In Scheme 1, conductive carbon black is used as the conductive carbon-based material. Its preparation process is as follows: Non-woven fabric was selected as the flexible substrate, and was ultrasonically cleaned with ethanol and then washed with deionized water before use. Weigh 1.15 g of conductive carbon black and 1.25 g of sodium dodecylbenzenesulfonate and add them to 100 mL of deionized water. Use a probe-type ultrasonic treatment for 50 min to obtain a uniform and stable conductive carbon black dispersion. The pretreated nonwoven fabric was immersed in the dispersion and thoroughly impregnated under continuous stirring at 800 rpm, and then dried at 60 ℃ for 45 min. The impregnation-drying cycle was repeated 5 times to obtain a conductive carbon black-loaded nonwoven film. Subsequently, a 5% (w / v) polyethyleneimine methanol solution was used for drop-coating modification, and the film was dried under vacuum at 70 °C for 30 min to obtain a polyethyleneimine-modified conductive carbon black-loaded nonwoven film.
[0048] In Scheme Two, acetylene black is used as the conductive carbon-based material. Its preparation process is as follows: Non-woven fabric was selected as the flexible substrate, and was ultrasonically cleaned with ethanol and then washed with deionized water before use. Weigh 1.14 g of acetylene black and 0.99 g of sodium dodecylbenzenesulfonate and add them to 100 mL of deionized water. Use a probe-type ultrasonic treatment for 35 min to obtain a uniform and stable acetylene black dispersion. The pretreated nonwoven fabric was immersed in the acetylene black dispersion and fully impregnated under continuous stirring at 800 rpm, and then dried at 60 ℃ for 1 h. The impregnation-drying cycle was repeated 5 times to obtain an acetylene black-loaded nonwoven film. Subsequently, a 5% (w / v) polyethyleneimine methanol solution was used for drop-coating modification, and the film was dried under vacuum at 70 °C for 30 min to obtain a polyethyleneimine-modified acetylene black-loaded nonwoven film.
[0049] In Scheme 3, a mixture of Ketjen black and conductive carbon black is used as the conductive carbon-based material. The preparation process is as follows: Non-woven fabric was selected as the flexible substrate, and was ultrasonically cleaned with ethanol and then washed with deionized water before use. In one method, 0.48 g of Ketjen black, 0.46 g of conductive carbon black and 1.12 g of sodium dodecylbenzenesulfonate were added to 100 mL of deionized water and subjected to ultrasonic treatment with a probe for 60 min to obtain a uniform and stable mixed carbon black dispersion. The pretreated nonwoven fabric was immersed in the dispersion and fully impregnated under continuous stirring at 1000 rpm, and then dried in an environment of 60 ℃ for 45 min. The impregnation-drying cycle was repeated 5 times to obtain a Ketjen black / conductive carbon black mixed-loaded nonwoven film. Subsequently, a 5% (w / v) polyethyleneimine methanol solution was used for drop-coating modification, and the film was dried under vacuum at 70 °C for 30 min to obtain a polyethyleneimine-modified Ketjen black / conductive carbon black mixed-load nonwoven film.
[0050] In Scheme Four, a mixture of Ketjen black and acetylene black is used as the conductive carbon-based material. The preparation process is as follows: Non-woven fabric was selected as the flexible substrate, and was ultrasonically cleaned with ethanol and then washed with deionized water before use. Add 0.43 g Ketjen black, 0.54 g acetylene black and 1.25 g sodium dodecylbenzene sulfonate to 100 mL of deionized water and treat with probe-type ultrasonic treatment for 50 min to obtain a uniform and stable mixed carbon black dispersion. The pretreated nonwoven fabric was immersed in the dispersion and thoroughly impregnated under continuous stirring at 800 rpm, and then dried at 65 ℃ for 30 min. The impregnation-drying cycle was repeated 6 times to obtain a Ketjen Black / acetylene Black mixed-loaded nonwoven film. Subsequently, a 5% (w / v) polyethyleneimine methanol solution was used for drop-coating modification, and the film was dried under vacuum at 70 °C for 30 min to obtain a polyethyleneimine-modified Ketjen black / acetylene black mixed-load nonwoven film.
[0051] In Scheme 5, a mixture of Ketjen black, conductive carbon black, and acetylene black is used as the conductive carbon-based material. The preparation process is as follows: Non-woven fabric was selected as the flexible substrate, and was ultrasonically cleaned with ethanol and then washed with deionized water before use. 0.51 g Ketjen black, 0.55 g conductive carbon black, 0.49 g acetylene black and 1.56 g sodium dodecylbenzene sulfonate were added to 150 mL of deionized water and treated with probe-type ultrasonication for 90 min to obtain a uniform and stable mixed carbon black dispersion. The pretreated nonwoven fabric was immersed in the dispersion and thoroughly impregnated under continuous stirring at 850 rpm, and then dried at 65 ℃ for 30 min. The impregnation-drying cycle was repeated 7 times to obtain a nonwoven film loaded with a mixture of Ketjen black / conductive carbon black / acetylene black. Subsequently, a 5% (w / v) polyethyleneimine methanol solution was used for drop-coating modification, and the film was dried under vacuum at 70 °C for 30 min to obtain a polyethyleneimine-modified ternary mixed carbon black loaded nonwoven film.
[0052] This embodiment illustrates that the carbon black material in the first carbon-based thin film can be one or more of Ketjen black, conductive carbon black, and acetylene black.
[0053] Example 7 This embodiment provides a preferred method for preparing a second carbon-based thin film. The second carbon-based thin film is a 6 M nitric acid-treated graphite thin film. The preparation process is as follows: Commercial graphite film was selected as the substrate and cut into 3×9 cm pieces. 2 The long strips were cleaned with ethanol and then dried to obtain a pretreated graphite film; The pretreated graphite film was immersed in 6 M nitric acid solution and treated at room temperature for 36 h. After processing, remove the graphite membrane and rinse it repeatedly with deionized water until the filtrate is neutral. The graphite film was then dried at 50 °C for 1 h to obtain a 6 M nitric acid-treated graphite film.
[0054] After treatment with nitric acid, the surface chemical state, wettability, and work function of the graphite film change, thereby enabling it to form an electronic structure difference with the first carbon-based film modified with polyethyleneimine.
[0055] The nitric acid-treated graphite film obtained in this embodiment is preferred as a second carbon-based film.
[0056] Example 8 This embodiment provides an untreated graphite film, used as a comparative example of a second carbon-based film. Its preparation process is as follows: Commercial graphite film was selected as the substrate and cut into 3×9 cm pieces. 2 The long strips were cleaned with ethanol and then dried to obtain the original graphite film.
[0057] The original graphite film obtained in this embodiment can be paired with a first carbon-based film that is either unmodified or modified with polyethyleneimine to verify the effect of the surface conditioning treatment of the second carbon-based film on the work function difference and device output performance.
[0058] Example 9 This embodiment provides a method for preparing graphite films treated with different nitric acid concentrations to illustrate the effect of nitric acid concentration on the surface state of the second carbon-based film and the output performance of the device.
[0059] Pretreated graphite films were prepared according to the pretreatment method described in Example 8. They were then treated with 2 M and 16 M nitric acid solutions, respectively.
[0060] In the case of treatment with 2 M nitric acid, the pretreated graphite film was immersed in a 2 M nitric acid solution and treated at room temperature for 48 h. After treatment, it was repeatedly rinsed with deionized water until the filtrate was neutral and dried at 50 ℃ for 45 min to obtain the 2 M nitric acid treated graphite film.
[0061] When treated with 16 M nitric acid, the pretreated graphite film was immersed in a 16 M nitric acid solution and treated at room temperature for 22 h. After treatment, it was repeatedly rinsed with deionized water until the filtrate was neutral and dried at 50 ℃ for 50 min to obtain the 16 M nitric acid-treated graphite film.
[0062] Comparing the graphite film obtained in this embodiment with the 6 M nitric acid-treated graphite film obtained in Example 8 can help determine the preferred range of nitric acid treatment concentration. Preferably, the nitric acid concentration is 6 M.
[0063] Example 10 This embodiment provides a solution for treating graphite films using other acidic solutions.
[0064] In one approach, a hydrochloric acid solution is used to treat the graphite film. The preparation process is as follows: Commercial graphite film was selected as the substrate and cut into 3×9 cm pieces. 2 The long strips were cleaned with ethanol and then dried to obtain a pretreated graphite film; The pretreated graphite film was immersed in 6 M hydrochloric acid solution and treated at room temperature for 36 h. After treatment, rinse repeatedly with deionized water until the filtrate is neutral; The graphite film was then dried at 50 °C for 1 h to obtain hydrochloric acid-treated graphite film.
[0065] In another approach, the graphite film is treated with a sulfuric acid solution. The preparation process is as follows: Commercial graphite film was selected as the substrate and cut into 3×9 cm pieces. 2 The long strips were cleaned with ethanol and then dried to obtain a pretreated graphite film; The pretreated graphite film was immersed in 2 M sulfuric acid solution and treated at room temperature for 24 h. After treatment, rinse repeatedly with deionized water until the filtrate is neutral; The graphite film was then dried at 50 °C for 60 min to obtain sulfuric acid-treated graphite film.
[0066] This embodiment illustrates that, in addition to nitric acid, other acidic solutions can also be used to regulate the surface state of graphite films, but considering the overall output performance and material structural stability, nitric acid treatment is the preferred method.
[0067] Example 11 This embodiment provides four treatment schemes for oxidized modified graphite films other than those in Example 7.
[0068] In Scheme 1, ultraviolet irradiation is used to treat the graphite film. The preparation method is as follows: Commercial graphite film was selected as the substrate and cut into 3×9 cm pieces. 2 The long strips were cleaned with ethanol and then dried to obtain a pretreated graphite film; After preheating the ultraviolet irradiation equipment, the pretreated graphite film was placed in it and irradiated from the front for 25 minutes and from the back for 25 minutes to obtain the ultraviolet-irradiated graphite film.
[0069] In Scheme Two, a salt solution is used to treat the graphite film. The preparation process is as follows: Commercial graphite film was selected as the substrate and cut into 3×9 cm pieces. 2 The long strips were cleaned with ethanol and then dried to obtain a pretreated graphite film; The pretreated graphite film was immersed in a saturated CaCl2 solution and treated at room temperature for 12 h. After treatment, rinse with deionized water to remove excess CaCl2 from the surface; The graphite film was then dried at 100 °C for 12 h to obtain a salt solution-treated graphite film.
[0070] In Scheme 3, a combined treatment of acid treatment and ultraviolet irradiation is used. The preparation process is as follows: Commercial graphite film was selected as the substrate and cut into 3×9 cm pieces. 2 The long strips were cleaned with ethanol and then dried to obtain a pretreated graphite film; The pretreated graphite film was immersed in 6 M nitric acid solution and treated at room temperature for 38 h. After treatment, the solution was washed until neutral and dried at 50 °C for 60 min to obtain an acid-treated graphite film. The acid-treated graphite film was then subjected to ultraviolet irradiation, with the front side irradiated for 30 minutes and the back side irradiated for 30 minutes, to obtain a graphite film with combined acid treatment and ultraviolet irradiation treatment.
[0071] In Scheme Four, a combined treatment of salt solution and ultraviolet irradiation is employed. The preparation process is as follows: Commercial graphite film was selected as the substrate and cut into 3×9 cm pieces. 2 The long strips were cleaned with ethanol and then dried to obtain a pretreated graphite film; The pretreated graphite film was immersed in a saturated CaCl2 solution and treated at room temperature for 12 h. After treatment, excess CaCl2 on the surface was removed by rinsing, and the film was dried at 100 °C for 12 h to obtain a salt-treated graphite film. Subsequently, it was subjected to ultraviolet irradiation treatment, with the front side irradiated for 25 minutes and the back side irradiated for 25 minutes, to obtain a graphite film with combined salt solution treatment and ultraviolet irradiation treatment.
[0072] This embodiment illustrates that the surface of the second carbon-based thin film can be modulated by acid treatment, ultraviolet irradiation, salt solution treatment or composite treatment to change its surface state or electronic structure.
[0073] Example 12 This embodiment provides a method for preparing a non-ionic hygroscopic hydrogel used in an air-humidity driven mode. The non-ionic hygroscopic hydrogel is preferably a polyvinyl alcohol / glycerol hydrogel. The preparation process is as follows: 8.7 g of glycerol was mixed with 11.5 g of deionized water to form a binary solvent, and 2.3 g of polyvinyl alcohol was added. The mixture was heated in a water bath at 90 °C for 8 h to obtain a transparent and homogeneous polyvinyl alcohol / glycerol treatment solution. The above polyvinyl alcohol / glycerol treatment solution was poured into a 2 mm high square mold and left to stand for 48 h at 25 ℃ and 45% relative humidity to cool and form a gel, resulting in a 2 mm thick polyvinyl alcohol / glycerol hydrogel.
[0074] The polyvinyl alcohol / glycerol hydrogel can adsorb ambient moisture and form a hydration transport channel between the first and second carbon-based films. Simultaneously, the polyvinyl alcohol / glycerol hydrogel itself does not introduce significant additional mobile ions; its main functions are moisture absorption, water storage, and maintaining a water-containing transport environment between the two carbon-based films.
[0075] The polyvinyl alcohol / glycerol hydrogel obtained in this embodiment is used as the aqueous medium in a hydrovoltaic power generation system under wet-driven mode.
[0076] Example 13 To illustrate the effect of hydrogel thickness on the air moisture-driven mode, polyvinyl alcohol / glycerol hydrogels with thicknesses of 4 mm and 7 mm were also prepared.
[0077] The preparation process of the 4 mm thick polyvinyl alcohol / glycerol hydrogel is as follows: 8.3 g of glycerol and 10.5 g of deionized water are mixed to form a binary solvent, 2.1 g of polyvinyl alcohol is added, and the mixture is heated in a water bath at 85 ℃ for 10 h to obtain a transparent and uniform polyvinyl alcohol / glycerol treatment solution; the above treatment solution is poured into a 4 mm high square mold and left to stand at 20 ℃ and 35% relative humidity for 50 h to cool and form a gel.
[0078] The preparation process of 7 mm thick polyvinyl alcohol / glycerol hydrogel is as follows: 8.2 g of glycerol and 10.8 g of deionized water are mixed to form a binary solvent, 2.5 g of polyvinyl alcohol is added, and the mixture is heated in a water bath at 90 ℃ for 8 h to obtain a transparent and uniform polyvinyl alcohol / glycerol treatment solution; the above treatment solution is poured into a 7 mm high square mold and left to stand at 30 ℃ and 45% relative humidity for 46 h to cool and form a gel.
[0079] Hydrogels of varying thicknesses can be used to represent the spacing between carbon-based thin films in moisture-driven thin-film hydrovoltaic power generation systems.
[0080] Example 14 This embodiment provides an assembly method for a hydroelectric power generation system driven by liquid water.
[0081] The polyethyleneimine-modified Ketjen black-loaded nonwoven fabric film prepared in Example 2 was selected as the first carbon-based film, and the 6 M nitric acid-treated graphite film prepared in Example 7 was selected as the second carbon-based film. The first and second carbon-based films were spaced apart and simultaneously contacted with liquid water. Then, they were connected to external circuits to obtain a liquid water-driven hydrovoltaic power generation system.
[0082] To illustrate the effect of the spacing between the first and second carbon-based thin films on the liquid water-driven mode, three film spacings of 5 mm, 15 mm, and 25 mm were used. The 5 mm spacing used a 1.1×1.5×1.2 cm³ square measuring mold; the 15 mm spacing used a 1.1×2.5×1.2 cm³ square measuring mold; and the 25 mm spacing used a 1.1×3.5×1.2 cm³ square measuring mold. By fixing the first and second carbon-based thin films into their respective molds and connecting them with test clips, liquid water-driven photovoltaic power generation systems with different spacings can be formed.
[0083] It should be noted that the work function is typically the surface electron work function measured under vacuum or dry conditions using ultraviolet photoelectron spectroscopy or a Kelvin probe. When a carbon-based thin film is immersed in liquid water or comes into contact with an aqueous medium, an electric double layer forms at the solid-liquid interface, and adsorbed polar molecules or ions may alter the effective electron work function of the surface. However, for the two carbon-based thin films of this invention with differentiated surface modulation (one side modified with an amine polymer, resulting in a lower work function; the other side modified with oxidation, resulting in a higher work function), even when completely immersed in liquid water or in contact with a hydrogel, the relative work function difference between the two remains unchanged, and the direction remains the same. This is because the chemical properties of the surface modification layer (such as the amine groups of PEI, or the oxygen-containing functional groups introduced by oxidation) remain stable in an aqueous environment, and the difference in electronic structure between the two still exists, thus maintaining a sufficient built-in electric field at the hydrated interface. Experimental evidence is as follows: Figure 2 As shown, after surface conditioning, the work function difference between the two films increased from 0.18 eV to 1.10 eV under drying conditions, while the output voltage in the liquid water test increased from about 0.35 V to about 1.1 V, indicating that the effective work function difference in the liquid phase is consistent with the trend measured under drying conditions.
[0084] Example 15 This embodiment provides an assembly method for a hydroelectric power generation system in an air-humidity driven mode.
[0085] The polyethyleneimine-modified Ketjen black loaded nonwoven film prepared in Example 2 was selected as the first carbon-based film, the polyvinyl alcohol / glycerol hydrogel prepared in Example 12 was selected as the aqueous medium, and the 6 M nitric acid-treated graphite film prepared in Example 7 was selected as the second carbon-based film.
[0086] A first carbon-based film, a polyvinyl alcohol / glycerol hydrogel, and a second carbon-based film are sequentially stacked, with the polyvinyl alcohol / glycerol hydrogel located between the first and second carbon-based films. The interlayer bonding is achieved using the adhesive properties of the hydrogel itself, and a breathable encapsulation material is used for fixation, resulting in a flexible air-moisture driven hydrovoltaic power generation system.
[0087] Example 16 This embodiment provides a modular integration approach. When multiple liquid water-driven photovoltaic power generation systems are connected in series, the output voltage increases approximately linearly with the number of units; when multiple moisture-driven photovoltaic power generation systems are connected in parallel, the output current is significantly increased. Depending on different power consumption scenarios, series, parallel, or hybrid series-parallel connection methods can be used to obtain high voltage or high current output.
[0088] In this invention, the work function difference refers to the difference between the surface work functions of the first carbon-based thin film and the second carbon-based thin film. The work function can be obtained by ultraviolet photoelectron spectroscopy or Kelvin probe microanalysis. Modifying the first carbon-based thin film with an amine polymer can reduce its surface work function; oxidizing the second carbon-based thin film can increase its surface work function, thereby creating an electronic structural asymmetry between the two carbon-based thin films and achieving directional electrical output in the presence of an aqueous medium.
[0089] To verify the impact of work function difference on device output performance, the unmodified Ketjen black loaded nonwoven film prepared in Example 3 was paired with the original graphite film prepared in Example 8, and the polyethyleneimine-modified Ketjen black loaded nonwoven film prepared in Example 2 was paired with the 6 mol / L nitric acid-treated graphite film prepared in Example 7. These were then assembled into liquid water-driven photovoltaic power generation systems. The test results are as follows: Figure 2 As shown, after modification with polyethyleneimine, the work function of the first carbon-based thin film decreased from approximately 4.55 eV to approximately 3.91 eV; after nitric acid treatment, the work function of the second carbon-based thin film increased from approximately 4.37 eV to approximately 5.01 eV; the difference in work function between the two carbon-based thin films increased from approximately 0.18 eV to approximately 1.10 eV. Correspondingly, the device output voltage increased from approximately 0.35 V to approximately 1.1 V, indicating that differential surface modulation can effectively increase the difference in work function between the two carbon-based thin films and regulate the output voltage of the hydrovoltaic power generation system.
[0090] To illustrate the impact of the composition of the first carbon-based thin film material on the device output performance, the polyethyleneimine-modified Ketjen black-loaded nonwoven film prepared in Example 2, and the polyethyleneimine-modified carbon nanotube composite film and polyethyleneimine-modified graphite film prepared in Example 5 were used as the first carbon-based thin film, and paired with the nitric acid-treated graphite film prepared in Example 7. The test results are as follows: Figure 3 As shown in Figure a, different conductive carbon-based materials can be used to construct liquid water-driven hydrovoltaic power generation systems with work function differences. Among them, compared with tightly layered graphite films and carbon nanotube composite films, porous fiber-structured Ketjen black-loaded nonwoven fabric films are more conducive to polyethyleneimine modification and solid-liquid interface contact, thus their corresponding devices exhibit superior output performance.
[0091] To optimize the surface modification conditions of the first carbon-based film, in conjunction with Examples 2 and 4, 1% (w / v), 5% (w / v), and 12.5% (w / v) polyethyleneimine solutions were used to modify the Ketjen black-loaded nonwoven film, respectively. The test results are as follows: Figure 3As shown in b, when the polyethyleneimine concentration is 1% (w / v), the number of amino functional groups introduced onto the film surface is limited, and the improvement in device output is not significant. With the increase of the polyethyleneimine mass-volume fraction, the device output voltage gradually increases. When the polyethyleneimine mass-volume fraction is 5% (w / v), the device exhibits superior overall performance. Further increasing the polyethyleneimine concentration causes the device output voltage change to plateau, indicating that the surface modification effect is nearing saturation. Meanwhile, excessive polyethyleneimine may form a thick coating layer on the surface of the Ketjen black-loaded nonwoven film, thereby obscuring some porous structures and active sites, which is detrimental to interfacial mass transfer and moisture diffusion. Therefore, considering both device output performance and sample preparation feasibility, 5% (w / v) polyethyleneimine is preferred as the surface modification condition for the first carbon-based film.
[0092] To illustrate the effect of carbon black materials on the performance of the first carbon-based film, carbon black-loaded nonwoven films were prepared using Ketjen black, conductive carbon black, acetylene black, and mixtures of the above carbon blacks, respectively, in conjunction with Examples 2 and 6. These films were then modified with polyethyleneimine and used as the first carbon-based film. The test results are as follows: Figure 3 As shown in Figure c, the first carbon-based thin films prepared using different carbon black materials can all form a liquid water-driven hydrovoltaic power generation system with the second carbon-based thin film. Among them, Ketjenblack, due to its large specific surface area and good charge loading capacity, produces a first carbon-based thin film device with relatively superior output performance.
[0093] To optimize the surface conditioning conditions of the second carbon-based thin film, graphite films were treated with 2 mol / L, 6 mol / L, and 16 mol / L nitric acid solutions, respectively, in conjunction with Examples 7 and 9. The test results are as follows: Figure 4 As shown in Figure a, when the nitric acid concentration is too low, the oxidation and functionalization of the graphite film surface are insufficient, making it difficult to effectively regulate its surface chemical state and electronic structure, thus limiting the improvement in device output. With increasing nitric acid concentration, the oxidation modification effect on the graphite film surface gradually strengthens, and the device performance improves accordingly. When the nitric acid concentration is 6 mol / L, the device output reaches a relatively optimal level. Further increasing the nitric acid concentration leads to a decrease in device performance, indicating that excessive oxidation may damage the graphite sheet structure, thereby affecting the stable output of the device. Therefore, considering both the oxidation modification effect and the material structural stability, a 6 mol / L nitric acid solution is preferred as the treatment condition for the second carbon-based thin film.
[0094] Different surface treatment methods affect the output performance of the corresponding liquid water-driven photovoltaic power generation system, as well as the treatment effects of the second carbon-based thin film. Further comparisons were made between hydrochloric acid treatment, sulfuric acid treatment, ultraviolet irradiation treatment, salt solution treatment, and composite treatment methods, based on Examples 10 and 11. The test results are as follows: Figure 4As shown in b, different oxidation modifications or surface modulation methods all affect the output performance of the corresponding devices based on the second carbon-based thin film. Among these, acid treatment can effectively modulate the surface state and electronic structure of the graphite thin film. Further... Figure 4 As shown in Figure c, the treatment effects of different acid solutions vary. Hydrochloric acid solution has weak oxidizing power and its effect on regulating the surface state and electronic structure of graphite films is limited; sulfuric acid solution has strong oxidizing power, but excessive treatment may affect the structural integrity of the graphite film. Considering the surface regulation effect, output performance, and film structural stability, nitric acid treatment is the preferred method.
[0095] The polyethyleneimine-modified Ketjen black-loaded nonwoven fabric film prepared in Example 2 was selected as the first carbon-based film, and the 6 mol / L nitric acid-treated graphite film prepared in Example 7 was selected as the second carbon-based film. A liquid water-driven hydrovoltaic power generation system was assembled according to the method described in Example 14. Test results are as follows: Figure 5 a and Figure 5 As shown in b, under deionized water conditions, the open-circuit voltage of a single liquid water-driven hydrovoltaic power generation system is approximately 1.1 V, and the short-circuit current density is approximately 450 μA·cm. -2 The device can still achieve effective output under tap water and simulated seawater conditions. Furthermore, such as... Figure 5 As shown in c, when the distance between the two carbon-based films increases from 5 mm to 25 mm, the output voltage changes little, while the output current decreases significantly, indicating that the output current is more susceptible to the influence of ion migration paths and interfacial transport resistance in the liquid water driven mode.
[0096] To extend the device's operating conditions to humid environments, the polyvinyl alcohol / glycerol nonionic hygroscopic hydrogel prepared in Example 12 was used as the hygroscopic and water-containing medium. This nonionic hygroscopic hydrogel can provide a stable water-containing environment for the humid drive mode without significantly altering the ion source. Following the method described in Example 15, the first carbon-based film prepared in Example 2, the hydrogel, and the second carbon-based film prepared in Example 7 were sequentially stacked and assembled to obtain the humid drive hydrovoltaic power generation system. Test results are as follows... Figure 6 As shown in Figure a, under conditions of 25 °C and 60% relative humidity, a single air-moisture driven hydroelectric power generation system can achieve an open-circuit voltage of approximately 1.0 V and an open-circuit voltage of approximately 350 μA·cm. -2 The short-circuit current density.
[0097] Combining Examples 12 and 13, polyvinyl alcohol / glycerol hydrogels with thicknesses of 2 mm, 4 mm, and 7 mm were prepared and assembled into an air-moisture-driven hydrovoltaic power generation system. Test results are as follows: Figure 6As shown in b, variations in hydrogel thickness have a relatively small impact on the output voltage, but a more significant impact on the output current. This is because a larger hydrogel thickness prolongs the transport path of migratable ions at the interface, thereby increasing charge dispersion and energy loss during transport, which is detrimental to current output. Considering both output performance and assembly convenience, a hydrogel thickness of 2 mm is preferred. Further test results are shown in... Figure 6 c and Figure 6 As shown in d, the device output current increases with the increase of effective area and also increases with the increase of ambient relative humidity, indicating that the air-humidity driven hydrovoltaic power generation system has area amplification response characteristics and humidity response characteristics.
[0098] The water-based photovoltaic power generation system described in this invention can also be modularly integrated according to Embodiment 16. Multiple liquid water-driven or air-moisture-driven water-based photovoltaic power generation systems can be connected in series, parallel, or series-parallel configurations, where series connection is used to increase the output voltage and parallel connection is used to increase the output current. Test results are as follows: Figure 7 a to Figure 7 As shown in c, multiple air-moisture driven hydrovoltaic power generation systems can be connected in series, parallel, or stacked to obtain higher voltage output, higher current output, or array-type output, respectively.
[0099] Furthermore, in conjunction with Examples 15 and 16, the air-humidity driven hydroelectric power generation system can maintain effective output under straight, bent, and torsional conditions, as shown in the test results. Figure 8 As shown in a; the power-generating thin film maintains a high output level even after being stored for a certain period of time, as shown in the test results. Figure 8 As shown in b; the power generation module can also be designed in different geometries or configurations according to application requirements, such as Figure 8 As shown in c in the figure. The application test results are as follows: Figure 9 and Figure 10 As shown, multiple liquid water drive units connected in series can charge commercial capacitors and drive small electronic devices, while multiple air humidity drive units connected in series can be used to drive low-power electronic devices. These results demonstrate that this invention achieves dual-mode hydrovoltaic power generation in both liquid water and air humidity environments by constructing an asymmetric carbon-based thin-film interface with a work function difference, and can improve output capacity through modular integration.
[0100] In this specification, the terms "one embodiment," "some embodiments," "example," "specific example," or "some examples," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment of the invention. Without contradiction, the described specific features, structures, materials, or characteristics may be combined in any suitable manner in one or more embodiments or examples.
[0101] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit the scope of protection of the present invention. For those skilled in the art, any equivalent substitutions, modifications, or improvements made to the present invention without departing from the concept of the present invention should fall within the scope of protection of the present invention. The scope of protection of the present invention is determined by the appended claims.
Claims
1. A carbon-based thin-film dual-mode hydrovoltaic power generation system based on work function difference regulation, characterized in that, It includes several carbon-based thin films, with an aqueous medium disposed between two adjacent carbon-based thin films; Two adjacent carbon-based thin films undergo different surface conditioning treatments to create a power function difference between them. Several carbon-based thin films are respectively brought into contact with an aqueous medium to form an interface, and then connected to an external circuit to form a hydroelectric power generation system; The hydroelectric power generation system has a liquid water driven power generation mode and an air moisture driven power generation mode; when it is a liquid water driven power generation mode, the water-containing medium is liquid water; when it is an air moisture driven power generation mode, the water-containing medium is a non-ionic hygroscopic hydrogel.
2. The carbon-based thin-film dual-mode hydrovoltaic power generation system based on work function difference control according to claim 1, characterized in that, Two different carbon-based thin films are referred to as the first carbon-based thin film and the second carbon-based thin film. Both the first carbon-based thin film and the second carbon-based thin film are made of conductive carbon-based materials. The surface conditioning treatment of the first carbon-based thin film is amine polymer surface modification, and the surface conditioning treatment of the second carbon-based thin film is oxidation modification treatment.
3. A carbon-based thin-film dual-mode hydrovoltaic power generation system based on work function difference control according to claim 2, characterized in that, The conductive carbon-based material used in the first carbon-based thin film is selected from one of carbon black composite materials, carbon nanotube composite materials, or graphite composite materials, while the conductive carbon-based material used in the second carbon-based thin film is graphite composite material.
4. A carbon-based thin-film dual-mode hydrovoltaic power generation system based on work function difference control according to claim 3, characterized in that, The surface of the amine polymer is modified with polyethyleneimine at a concentration of 1% (w / v) to 12.5% (w / v).
5. A carbon-based thin-film dual-mode hydrovoltaic power generation system based on work function difference control according to claim 4, characterized in that, Oxidative modification treatment includes one or more of acid treatment, ultraviolet irradiation, and salt solution doping.
6. A carbon-based thin-film dual-mode hydrovoltaic power generation system based on work function difference control according to claim 5, characterized in that, In the liquid water driven mode, the first carbon-based film and the second carbon-based film are spaced apart and simultaneously in contact with liquid water; in the air moisture driven mode, the first carbon-based film, the non-ionic hygroscopic hydrogel, and the second carbon-based film are stacked sequentially.
7. A method for preparing a carbon-based thin-film dual-mode hydrovoltaic power generation system based on work function difference control, the method being used to prepare the carbon-based thin-film dual-mode hydrovoltaic power generation system based on work function difference control as described in any one of claims 1 to 6, characterized in that, The method includes the following steps: A methanol solution containing polyethyleneimine was applied to the surface of a conductive carbon-based material sheet and dried to obtain a first carbon-based thin film. A conductive carbon-based material sheet is immersed in an acid solution at room temperature; after immersion, the conductive carbon-based material sheet is washed until neutral and then dried to obtain a second carbon-based film. Polyvinyl alcohol, glycerin and deionized water are mixed and heated to dissolve, then poured into a mold to cool and solidify into a gel, resulting in a nonionic hygroscopic hydrogel. A dual-mode hydrovoltaic power generation system is obtained by alternately setting up several first carbon-based thin films and several second carbon-based thin films, and placing a non-ionic hygroscopic hydrogel between the first carbon-based thin films and the second carbon-based thin films.
8. The method for preparing a carbon-based thin-film dual-mode hydrovoltaic power generation system based on work function difference control according to claim 7, characterized in that, A methanol solution containing polyethyleneimine is applied to the surface of a conductive carbon-based material sheet and dried to obtain a first carbon-based thin film. The specific steps for obtaining the first carbon-based thin film are as follows: A polyethyleneimine methanol solution with a mass-volume fraction of 1%~12.5% (m / v) was prepared and drop-coated onto the surface of a conductive carbon-based material sheet. After vacuum drying at 70℃ for 20 min~120 min, the first carbon-based film was obtained.
9. The method for preparing a carbon-based thin-film dual-mode hydrovoltaic power generation system based on work function difference control according to claim 8, characterized in that, A conductive carbon-based material sheet is immersed in an acid solution at room temperature; after immersion, the conductive carbon-based material sheet is washed until neutral and then dried to obtain a second carbon-based film. The specific steps include the following: The conductive carbon-based material sheet was immersed in 2 mol / L to 16 mol / L nitric acid solution at room temperature for 22 h to 48 h, then repeatedly washed with deionized water until the filtrate was neutral, and dried at 50 °C to 65 °C for 45 min to 90 min to obtain the second carbon-based film.
10. The method for preparing a carbon-based thin-film dual-mode hydrovoltaic power generation system based on work function difference control according to claim 9, characterized in that, Polyvinyl alcohol, glycerin, and deionized water are mixed and heated to dissolve, then poured into a mold to cool and solidify into a gel, resulting in a nonionic hygroscopic hydrogel. The specific steps include the following: Glycerin at a mass ratio of 0.76 to 0.79 is mixed with deionized water to form a binary solvent. Polyvinyl alcohol solute at a mass ratio of 0.11 to 0.13 is added and mixed. The mixture is heated in a water bath at 85°C to 90°C for 8 to 10 hours to obtain a transparent polyvinyl alcohol solution. The polyvinyl alcohol solution is then poured into a mold and allowed to stand at 20°C to 30°C and 30% to 45% relative humidity for 46 to 50 hours to solidify into a gel, thus obtaining a polyvinyl alcohol / glycerin nonionic hygroscopic hydrogel.